Pengaruh Penambahan Serbuk Cangkang Kerang Terhadap Stabilisasi Tanah - Wirahadi Putra Ode; Sjafrudin Latar; Sulastri Kakaly (Jurnal Teknik Indonesia, 2026)
This study examines the effect of adding shell powder on the stabilization of clay soil in Taeno Hamlet, Ambon City, Maluku. The clay soil in this area has low bearing capacity, making it unsuitable for construction. Therefore, efforts are needed to improve soil quality through stabilization using oyster shell powder, which has the potential to improve the physical and mechanical properties of the soil. This study aims to determine the effect of adding Strombus luhuanus shell powder on the stabilization of clay soil. The method used was a laboratory experiment with variations in shell powder addition of 0%, 8%, 16%, and 24%, as well as curing periods of 0, 7, and 14 days. The tests conducted included moisture content, bulk density, specific gravity, Atterberg limits, sieve analysis, compaction test, and CBR test. The results of the study showed that the effect of adding oyster shell powder on the CBR test was highest at 0% (5.31%), followed by 8% (6.19%), 16% (6.92%), and 24% (7.50%). From the results obtained, the effect of adding oyster shell powder on soil stabilization showed an increase in CBR values starting from 0 days through the curing period of 7 to 14 days.